Comparative Feasibility Study Analysis Of Islamic And Conventional: Case Study Quail Farm In Pekanbaru - Hamdi Agustin (UIR Press, 2016)
The purporse this studies to compare the calculation of financial analysis on the feasibility of investments between the Islamic concepts of the conventional concept. In this study try to do research as the implications of this concept and examples of cases in the cattle business quail to enrich financial research that will find a new concept in the field of Islamic financial analysis business feasibility study. The result of reseach of the financial aspects of the show that a comparative analysis of the feasibility study that takes Islamic and conventional business case studies quail farm in Pekanbaru showed no difference in the decision to accept or reject by using both of these methods. This analysis shows the calculation method of shariah could be used in assessing the feasibility of investing can be used in the feasible study anayisis. The method of syariah are calculation Gold Value Method (GVM), Methods Gold Index (GI) and methods Investible Surplus Analysis Method.